Cell death in the Schwann cell lineage and its regulation by neuregulin. - Syroid, D E (1996)
The development of Schwann cells, the myelin-forming glial cells of the vertebrate peripheral nervous system, involves a neonatal phase of proliferation in which cells migrate along and segregate newly formed axons. Withdrawal from the cell cycle, around postnatal days 2-4 in rodents, initiates terminal differentiation to the myelinating state. During this time, Schwann cell number is subject to stringent regulation such that within the first postnatal week, axons and myelinating Schwann cells attain the one-to-one relationship characteristic of the mature nerve. The mechanisms that underly this developmental control remain largely undefined. In this report, we examine the role of apoptosis in the determination of postnatal Schwann cell number. We find that Schwann cells isolated from postnatal day 3 rat sciatic nerve undergo apoptosis in vitro upon serum withdrawal and that Schwann cell death can be prevented by beta forms of neuregulin (NRG-beta) but not by fibroblast growth factor 2 or platelet-derived growth factors AA and BB. This NRG-beta-mediated Schwann cell survival is apparently transduced through an ErbB2/ErbB3 receptor heterodimer. We also provide evidence that postnatal Schwann cells undergo developmentally regulated apoptosis in vivo. Together with other recent findings, these results suggest that Schwann cell apoptosis may play an important role in peripheral nerve development and that Schwann cell survival may be regulated by access to axonally derived NRG.